Modeling tools for detecting DoS attacks in WSNs. Issue 4 (14th February 2013) - Ballarini, Paolo; Mokdad, Lynda; Monnet, Quentin
ABSTRACT Detecting denial‐of‐service (DoS) attacks and reducing the energy consumption are two important and frequent requirements in wireless sensor networks (WSNs). In this paper, we propose an energy‐preserving solution to detect compromised nodes in hierarchically clustered WSNs. DoS detection is based on using dedicated inspector nodes (cNodes) whose role is to analyze the traffic inside a cluster and to send warnings to the cluster head whenever an abnormal behavior (i.e., high packets throughput) is detected. With previously introduced DoS detection schema, cNodes are statically displaced in strategic positions within the network topology. This guarantees good detection coverage but leads to quickly draining cNodes battery. In this paper, we propose a dynamic cNodes displacement schema according to which cNodes are periodically elected among ordinary nodes of each atomic cluster. Such a solution results in a better energy balance while maintaining good detection coverage. We analyze the tradeoffs between static and dynamic solutions by means of two complementary approaches: through simulation with the NS‐2 simulation platform and by means of statistical model checking with the Hybrid Automata Stochastic Logic. Copyright © 2013 John Wiley & Sons, Ltd.